2019
DOI: 10.1039/c9sc03717a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel [FeFe]-hydrogenases for biocatalytic H2-production

Abstract: A semi-synthetic screening method for mining the biodiversity of [FeFe]-hydrogenases, expanding the toolbox for biocatalytic H2-gas production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…To generate active hydrogenase in concentrations suitable for whole-cell spectroscopy, the HydA1 protein was heterologously expressed in BL21(DE3) E. coli cells, similar to previous reports. [44][45][46] The absence of the [FeFe]-hydrogenase specic maturation machinery in E. coli results in the synthesis of an inactive form of the enzyme containing the [4Fe-4S] H cluster but lacking the [2Fe] H subsite (apo-HydA1). 50 mL cell cultures were concentrated to 2 mL and depleted of O 2 at which point the synthetic cofactor mimic [2Fe] adt was added to the medium, and the H-cluster assembly monitored by EPR spectroscopy and H 2 production assays.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To generate active hydrogenase in concentrations suitable for whole-cell spectroscopy, the HydA1 protein was heterologously expressed in BL21(DE3) E. coli cells, similar to previous reports. [44][45][46] The absence of the [FeFe]-hydrogenase specic maturation machinery in E. coli results in the synthesis of an inactive form of the enzyme containing the [4Fe-4S] H cluster but lacking the [2Fe] H subsite (apo-HydA1). 50 mL cell cultures were concentrated to 2 mL and depleted of O 2 at which point the synthetic cofactor mimic [2Fe] adt was added to the medium, and the H-cluster assembly monitored by EPR spectroscopy and H 2 production assays.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that diverging reactivity was recently reported for two putative sensory [FeFe]-hydrogenases of different origin, which appear to stabilize in an H red -like state both in vitro and in whole cells. 46,50 This arguably reects the different physiological roles of sensory hydrogenases and the prototypical HydA1 enzyme. 51 In addition to the relatively stable catalytic intermediates H ox and H red , the study revealed complex metal-hydride chemistry occurring in living cells and two different hydride states were observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[66][67][68] Arguably, the main impact of artificial maturation to-date has been the simplified preparation of the active enzyme 60,69 including site-selective isotopologues, [70][71][72] which also facilitates rapid screening protocols. 30 Another important aspect is the preparation of [FeFe]-hydrogenases in which the diiron site is synthetically modified in order to generate non-natural H-clusters and enzymes with new properties. [73][74][75][76] In the case of Group A [FeFe]-hydrogenase, the active site cavity has been extensively explored through site-directed mutagenesis (Chapter 2.1.2).…”
Section: Artificial Maturation and Organometallic Variantsmentioning
confidence: 99%